An overview of oral mucosa condition of shisha smoker - Rahmi Amtha; Ardianto Kurniadi (Journal of Dentomaxillofacial Science, 2016)
Shisha is a water pipe that tobacco extract and fruit scented burnt using coal. It produces the smoke through the vessel and inhaled using a hose with good taste. The culture of shisha smoking is popular in Midle East country that curently has been also entering Indonesia. The side effect of shisha smoking habit is still very rare reported. Aim of this study is to describe the oral mucosa condition of shisha user. A preliminary observasional study was conducted at several sisha cafe at South Jakarta. Under informed consent, subject with habit of tobacco and shisha smoker were included. Sociodemographic data (age, gender, duration, frequency of smoking), salivary flow rate and oral mucosa changes were documented. Eighteen subjects were recruited into this study. Most of shisha smoker was also tobacco smoker. Shisha was more practiced by male atÂ  age (15-24 years old). The oral mucosa changes such as keratosis, melanosis, leukoedema, coated tongue, gingivitis and xerostomia were found on subject with habit of tobacco smoking habit only or both shisha and tobacco smoking. In conclusion apparently the shisha smoking habit may casue oral mucosa changes almost the same with tobacco smoking habit